Association of Parasite Biomass with Disease Severity in Plasmodium vivax and Plasmodium falciparum Malaria Infections - Prasad H. Babar; Jacob A. Tennessen; Rimi Chakrabarti; Jayashri T. Walke; Usheer Kanjee; Anvily Almeida; Mezia Fernandes; Pooja Gawas; Laura Karschney; John White; Marina Vaz; Edwin Gomes; et al. (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. The clinical and parasitological factors underlying severe malaria pathogenesis remain incompletely understood, particularly in Plasmodium vivax ( P. vivax ). To address this issue, clinical and parasitological metrics, including circulating peripheral parasitemia and the parasite biomass (the total number of parasites in the body consisting of both circulating peripheral and noncirculating parasites), were measured in patients with severe and uncomplicated monoinfections of P. vivax and Plasmodium falciparum ( P. falciparum ) malaria who presented at a hospital in southwest India. Peripheral parasitemia was positively correlated with disease severity in P. falciparum but negatively correlated with disease severity in P. vivax. Contrarily, the parasite biomass, estimated by the levels of circulating antigens P. vivax lactate dehydrogenase and P. falciparum histidine-rich protein 2 for P. vivax and P. falciparum, respectively, was positively correlated with both the degree of severity and the length of hospital stay in both P. vivax and P. falciparum cases. Together, these observations indicate a significant hidden parasite biomass in P. vivax infections and suggest that parasite biomass is a more robust parasitological marker of severity than parasitemia. Notably, thrombocytopenia was also positively correlated with parasite biomass and longer hospital stay in both P. vivax and P. falciparum infections. These results highlight the importance of parasite biomass as a leading factor in the disease severity of malaria infections in India.